Perfluorooctane sulfonate and bisphenol a strongly interact with bacterial antigens and adversely modulate host immunity - Wang, Mengjing (Nanyang Technological University, 2022)
Interactions between microbes and environmental pollutants are postulated to play a critical role in immune development; however, there is little evidence to substantiate this hypothesis. Early exposure to microbial lipopolysaccharide (LPS) protects against allergic asthma. Here we demonstrated that many ubiquitous environmental chemicals especially bisphenol A (BPA) and perfluorooctane sulfonate (PFOS), two common asthma-relevant chemicals, can effectively neutralize LPS at low levels (~10 nM, similar to that detected in human sera) to inhibit immunostimulatory activity of LPS both in vitro (11.0-28.2% relative to the LPS control) and in vivo (9.0-34.4% relative to the LPS control). The mechanistic study reveals that BPA and PFOS neutralize LPS through concomitant binding with the lipid A moiety. Furthermore, in an experimental asthma model of C57BL/6 and BALB/c mouse induced by house dust mite (HDM), BPA and PFOS both diminish the prophylactic effect of low dose LPS (100 ng) on asthma. In addition, PFOS itself was also found to bind and inhibit HDM’s immune stimulation. PFOS at 1.0 nM inactivated HDM by 22%. Such interplay provides a likely new explanation for children asthma induced by pollutants. Finally, using the experimental data set of the tested 40 chemicals’ LPS inactivation potencies, we were able to build one topological torsion-based random forest QSAR model to predict LPS inactivation by structurally diverse chemicals. In sum, we have found one novel interaction mechanism between environmental chemicals and common antigens, which has significant impact on the host immunity. Understanding the interaction between environmental chemicals and microbial components as well as its reshaping of innate immunity is important in developing prevention strategies against immune diseases associated with urbanization.